Ammonothermal Synthesis of Novel Nitrides: Case Study on CaGaSiN3 - Haeusler, Jonas; Neudert, Lukas; Mallmann, Mathias; Niklaus, Robin; Kimmel, Anna-Carina; Alt, Nicolas; Schlücker, Eberhard; Oeckler, Oliver; Schnick, Wolfgang (Chemistry - A European Journal, 2017)
The first gallium-containing nitridosilicate CaGaSiN was synthesized in newly developed high-pressure autoclaves using supercritical ammonia as solvent and nitriding agent. The reaction was conducted in an ammonobasic environment starting from intermetallic CaGaSi with NaN as a mineralizer. At 770 K, intermediate compounds were obtained, which were subsequently converted to the crystalline nitride at temperatures up to 1070 K (70–150 MPa). The impact of other mineralizers (e.g., LiN, KN, and CsN) on the product formation was investigated as well. The crystal structure of CaGaSiN was analyzed by powder X-ray diffraction and refined by the Rietveld method. The structural results were further corroborated by transmission electron microscopy, Si MAS-NMR, and first-principle DFT calculations. CaGaSiN crystallizes in the orthorhombic space group Cmc2 (no. 36) with lattice parameters a=9.8855(11), b=5.6595(1), c=5.0810(1) Å, (Z=4, R=0.0326), and is isostructural with CaAlSiN (CASN). Eu doped samples exhibit red luminescence with an emission maximum of 620 nm and FWHM of 90 nm. Thus, CaGaSiN:Eu also represents an interesting candidate as a red-emitting material in phosphor-converted light-emitting diodes (pc-LEDs). In addition to the already known substitution of alkaline-earth metals in (Ca,Sr)AlSiN:Eu, inclusion of Ga is a further and promising perspective for luminescence tuning of widely used red-emitting CASN type materials.
Keywords: ammonothermal synthesis; electron diffraction; luminescence; nitrides; nitridosilicates